Enhancing Walkability in Jakarta’s Transit Oriented Development (TOD): a Pathway to Optimizing First- and Last- Mile Mobility - Putra, Dimas Pramana; Hasibuan, Hayati Sari; Djaja, Bambang Marhaendra (Jurnal Pembangunan Wilayah dan Kota, 2025)
For Jakarta’s sustainable mobility transition, TOD (Transit-Oriented Development) success depends on seamless First-and-Last-Mile (FLM) connectivity. Specifically, high-quality walkability is essential to connect transit hubs to destinations and drive public transport adoption. This study investigates pedestrian behavior and infrastructure within Jakarta, Indonesia's Dukuh Atas TOD area, employing a quantitative descriptive approach. Data was collected through a survey of 400 respondents using accidental random sampling, observational studies, and the Pedestrian Environment Quality Index (PEQI). Analysis of commuter travel patterns reveals a predominance of work-related trips, reflecting its central business district function and high public transport usage. Health emerged as the dominant motivation for walking, outweighing cost factors, thereby underscoring the role of FLM connectivity in active commuting. Assessment of FLM connectivity highlights the importance of integrated transport solutions. Walkability near transit hubs is generally positive but require improvements in specific areas. Positive perceptions of pedestrian infrastructure—such as sidewalks, lighting, and vegetation—indicate opportunities for enhancement. These findings position Dukuh Atas as a model for effective TOD planning, highlighting the potential for infrastructure upgrades to promote walking and public transport use, contributing to more pedestrian-friendly and sustainable urban development.